GVIDI: A system to improve the safety of groups of hikers based on real-time monitoring and dataset generation - Iván García; Javier A. Albusac; José J. Castro-Schez; Vanesa Herrera; David Vallejo (SoftwareX, 2023)
The number of hikers has increased significantly in recent years, but so has the number of accidents. Software solutions have emerged to mitigate this problem, but most focus on monitoring individual activity. When hikers are not walking alone, their activities and decisions as a group have a major impact on their safety. This paper presents GVIDI, a novel system for monitoring real-time group activity in natural environments and generating datasets for forensic analysis. GVIDI software and data can be used by researchers to study how environmental conditions, events, and decisions affect the safety of expedition groups.